Pengaruh Jumlah Pengusaha Kena Pajak dan Lapor SPT PPN Terhadap Penerimaan PPN - Dinar Riftiasari (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This research aims to determine the effect of the number of Taxable Entrepreneurs and reporting VAT SPTs on VAT revenues by conducting partial and simultaneous research tests at KPP Pratama Jakarta Senen for the 2018-2022 period. The type of data used in this research is quantitative data with the data source being secondary data with data collection over 5 years. The sample in this research uses a saturated sampling technique, the data collection technique in this research is a documentation study, the data analysis tool used is with the help of the SPSS version 26 program and the data analysis technique in this research is the classic assumption test, hypothesis test and coefficient of determination test. The results of this research show that partially the number of Taxable Entrepreneurs has no effect on VAT receipts, reporting VAT SPTs has no effect on VAT receipts, while the simultaneous test results of the number of Taxable Entrepreneurs and reporting VAT SPTs have no effect on VAT receipts.